Introduction of the Method of Using Sleep Games in Dance Movements in the Development of Balance - Uralovna, Hakimova Nargiza (European Journal of Life Safety and Stability (2660-9630), 2021)
Athletics, fitness bases and the art of dance, which play an important role in the formation of a woman's stature, are also a guarantee of a beautiful stature. Proper performance of all physical exercises also contributes to the development of a mature and elegant human body.